Saratok District Council, Sarawak / Felicity Chinda James - James, Felicity Chinda (Universiti Teknologi MARA, Sarawak, 2019)
Saratok District Council was established in 1948 and firstly known as “Kalaka Mixed Local Authority”. The name was changed to “Kalaka District Council” in 1954. However, the name was change again to Saratok District Council in 1991. That name was last until today. Saratok District Council had its own office building in the year 1962 which was launched by Mr. Resident of the Second Division Simanggang, Mr. A.J.N. Richards. However, the building was demolished and builds again in 1991. The new building of the Saratok District Council was launched by YB Ministry of Environment and Tourism at that time which is Datuk Amar James Wong Kim Min on 23rd June 1993. From the year 1948 until 1953, the main office of Saratok District Council was situated at the Public Library. Then, it was transferred to the old building of government that situated at Masjid Besar, Saratok.